Novel model for calculating the interface heat flux between roller and molten steel/solidified shell during twin-roll strip casting - Jingzhou Lu; Wanlin Wang; Peisheng Lyu; Aihua Chen; Hualong Li (Case Studies in Thermal Engineering, 2025)
During the twin-roll strip casting (TRSC) process, molten steel rapidly cools on the copper roller surface, forming a sub-rapid solidified shell. The distribution of thermal resistance at the roller/steel interface is a critical factor influencing casting efficiency and product quality. To address this, a novel “process parameters - heat flux” (PPHF) model is proposed, which integrates roller/steel temperatures, deposited film, and air gap effects to predict spatial heat flux distribution under varying process conditions. Unlike traditional methods requiring in-situ temperature measurements, this model can directly calculate the heat flux along the roller arc. Validation via Q235 steel experiments on a TRSC test line confirmed an accuracy within 5 % error. Key findings demonstrate that the interface heat flux increases with the increasing casting speed and superheat. When the casting speed increases from 55 m/min to 65 m/min, the corresponding heat flux rises from 12.48 MW/m2 to 13.27 MW/m2. When the superheat increases from 30 °C to 90 °C, the corresponding heat flux rises from 12.12 MW/m2 to 13.83 MW/m2. The PPHF model can provide real-time heat flux prediction to support dynamic process control in industrial TRSC, bridging the gap between simulation and production optimization.